To solve the quadratic equation \(46x^2 - 138x = 0\) by factoring out the greatest common factor (GCF), we first identify the GCF of the terms in the equation.
The GCF of \(46x^2\) and \(-138x\) is \(46x\).
We can factor out \(46x\) from the equation:
\[ 46x(x - 3) = 0 \]
Now, we set each factor equal to zero:
-
\(46x = 0\)
This gives us \(x = 0\). -
\(x - 3 = 0\)
This gives us \(x = 3\).
Thus, the solutions to the equation are \(x = 0\) and \(x = 3\).
The correct answer is: The solutions are x = 0 and x = 3.